Convertible Bonds: Default Risk and Uncertain Volatility - Haishi Huang (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
Within a default intensity approach we discuss the optimal exercise of the callable and convertible bonds. Pricing bounds for convertible bonds are derived in an uncertain volatility model, i.e. when the volatility of the stock price process lies between two extreme values.
Keywords: G12; G33; 330; Convertible bond; game option; uncertain volatility; interest rate risk; Wandelanleihe; Wertpapieranalyse; Unternehmenswert; Börsenkurs; Volatilität; Kreditrisiko; Stochastischer Prozess; Theorie